I professionisti del sociale: crisi del welfare state, crisi economica - Gardini, Emilio; Ferraro, Stefania (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
This article analyzes the present condition of the professional social workers through their practice activities and their biographies. The context of the ethnographic research is Naples. The first part of the paper describes the experience of social operators that work in the cooperatives of the third sector and in the private social organizations. The second one presents a focus about the condition of the social workers that take care of the homeless. The theoretical perspective of this paper is the critical approach to the “selective welfare policy” produced by the liberal governmentality. The authors focus on the distortions created by the system of governance and its impact on social workers and “users”. From the point of view of professional social workers, this article reflects on how “work, health and family” become an “individual risk” as a result of the transformation of welfare policies.